Contrasting Controls on Microzooplankton Grazing and Viral Infection of Microbial Prey - Talmy, David; Beckett, Stephen J.; Zhang, Adam B.; Taniguchi, Darcy A. A.; Weitz, Joshua S.; Follows, Michael J. (Frontiers in Marine Science, 2019)
The encounter and capture of bacteria and phytoplankton by microbial predators and parasites is fundamental to marine ecosystem organization and activity. Here, we combined biophysical models with published laboratory measurements to infer functional traits, including encounter kernel and capture efficiency, for a wide range of marine viruses and microzooplankton grazers. Despite virus particles being orders of magnitude smaller than microzooplankton grazers, virus encounter kernels and adsorption rates were in many cases comparable in magnitude to grazer encounter kernel and clearance, pointing to Brownian motion as a highly effective method of transport for viruses. Inferred virus adsorption efficiency covered many orders of magnitude, but the median virus adsorption efficiency was between 5 to 25% depending on the assumed host swimming speed. Uncertainty on predator detection area and swimming speed prevented robust inference of grazer capture efficiency, but sensitivity analysis was used to identify bounds on unconstrained processes. These results provide a common functional trait framework for understanding marine host-virus and predator-prey interactions, and highlight the value of theory for interpreting measured life-history traits.